2019
DOI: 10.1039/c9ob02116g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of fatty acid decarboxylation catalyzed by a non-heme iron oxidase (UndA): a QM/MM study

Abstract: QM/MM calculations reveal that the fatty acid decarboxylase UndA employs the FeIII–OO˙− complex to initiate the β-H abstraction with the monodentate coordination mode. The iron center accepts the extra electron of the substrate radical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…However, in point c the distance of O1···O2 suddenly decreases to 1.44 Å, and the distance of Fe2–O1 increases to 2.16 Å. In the previous studies of other nonheme enzymes, , this sudden change of the scanned energy was suggested to be caused by the electron transfer or reorganization. Thus, we further calculated the spin densities of three key points in the PES.…”
Section: Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, in point c the distance of O1···O2 suddenly decreases to 1.44 Å, and the distance of Fe2–O1 increases to 2.16 Å. In the previous studies of other nonheme enzymes, , this sudden change of the scanned energy was suggested to be caused by the electron transfer or reorganization. Thus, we further calculated the spin densities of three key points in the PES.…”
Section: Results and Discussionmentioning
confidence: 83%
“…To further understand the OH-rebound reaction, we show the scanned energy profile in Figure 6. At the beginning from point a to point b, the energy of the system keeps increasing In the previous studies of other nonheme enzymes, 91,92 this sudden change of the scanned energy was suggested to be caused by the electron transfer or reorganization. Thus, we further calculated the spin densities of three key points in the PES.…”
Section: Resultsmentioning
confidence: 89%
“…2019 年, Zhang课题组 [34] 重新解析了Pf UndA的晶体结构, 提出的假设, 模式 III和IV分别基于Zhang课题组 [34] 和Fox课题组 [35] 的研 究. 在最新获得的Pf UndA晶体结构(PDB编号: 6P5Q) 基础上, 本课题组 [32] 通过手动添加O 2 使其与双铁中心 结合, 构建了几种包含O 2 的Fe 2 (III/III)及Fe 2 (IV/IV)复合…”
Section: Undaunclassified
“…虽然实 . (c) Six constructed models of Fe 2 (III/III) complexes and Fe 2 (IV/IV) intermediates [32] based on the crystal structure of Pf UndA (PDB ID: 6P5Q)…”
Section: 物 通过与另一种非血红素双铁酶Cado(pdb编号mentioning
confidence: 99%
“…6 3,5-Dihydroxyphenylacetyl-CoA 1,2-dioxygenase (DpgC) without cofactors and metal ions is universally used to biosynthesize an important class of vancomycin and teicoplanin antibiotics. 7 In contrast to the massive investigations on the catalytic mechanisms of metal-containing 8 or cofactor-containing 9 oxidases and oxygenases, the detailed mechanism regarding the molecular oxygen activation catalyzed by enzymes, which is performed without the aid of metal ions and cofactors, has been barely studied and hence remains unclear to date.…”
Section: Introductionmentioning
confidence: 99%